2011
DOI: 10.3851/imp1701
|View full text |Cite
|
Sign up to set email alerts
|

HBV Core Region Variability: Effect of Antiviral Treatments on Main Epitopic Regions

Abstract: Natural and treatment-induced substitutions in HBV core protein, occurring especially with interferon treatment, were characterized. Some immune-stimulating activity related to the minor Th28-47 epitope might be associated with nucleoside/nucleotide analogues; this activity was also seen in inactive carriers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 43 publications
2
3
0
Order By: Relevance
“…In contrast, preCore MfAA was not significantly different between any of the groups, which could indicate that the host immune response mainly acts against Core epitopes in patients with fluctuating HBeAg. In fact, preCore variants and positive selection of Core variants were common in HBeAg-negative and fluctuating patients, in keeping with results from our previous studies [8], [22]. These findings may result from HBV adaptation under host immune pressure, or even be due to an effect of antiviral treatment on the Core gene.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In contrast, preCore MfAA was not significantly different between any of the groups, which could indicate that the host immune response mainly acts against Core epitopes in patients with fluctuating HBeAg. In fact, preCore variants and positive selection of Core variants were common in HBeAg-negative and fluctuating patients, in keeping with results from our previous studies [8], [22]. These findings may result from HBV adaptation under host immune pressure, or even be due to an effect of antiviral treatment on the Core gene.…”
Section: Discussionsupporting
confidence: 90%
“…The region analyzed by UDPS, clustered positions 1757 to 2152 [16], covered the complete preCore (1814–1900) and the first 84 codons of the Core gene (1901–2152), which include the two main immunodominant epitopes flanked by amino acids 50 to 69 (Th 50–69) and by amino acids 74 to 84 (B74–84) [22].…”
Section: Methodsmentioning
confidence: 99%
“…These mutations in the BCP region are caused by deletions or insertions in the C-terminal leading to severe clinical outcomes in chronic participants. Previously, a study of HBV core variability among HAART participants, as in our study, suggested that the presence of the T67N mutation significantly reduced T-cell proliferation in vitro when it occurred with mutation E64D [59]. In our study, these mutations occurred both in combination and independent of each other.…”
Section: Discussionsupporting
confidence: 75%
“…In this study, the HBcAg mutations E64D, E77Q, A80I/T/V, and L116I were significantly associated with cirrhosis and HCC. Previously, a study of HBV core variability under antiviral therapy reported the presence of the E64D mutation during the course of HBV infection, and stated that this substitution significantly reduced T-cell proliferation in vitro when it occurred with mutation T67N (Homs et al, 2011 ). Similarly, the mutations associated with severe liver disease were reportedly concentrated in the center of HBcAg, in a region including amino acids 59–66 (Akarca and Lok, 1995 ).…”
Section: Discussionmentioning
confidence: 99%